Determinants of plasma docosahexaenoic acid levels and their relationship to neurological and cognitive functions in PKU patients: a double blind randomized supplementation study - Demmelmair, Hans; MacDonald, Anita; Kotzaeridou, Urania; Burgard, Peter; Gonzalez-Lamuno, Domingo; Verduci, Elvira; Ersoy, Melike; Gokcay, Gulden; Alyanak, Behiye; Reischl, Eva; Müller-Felber, Wolfgang; Faber, Fabienne Lara; et al. (Nutrients, 2018)
Children with phenylketonuria (PKU) follow a protein restricted diet with negligible amounts of docosahexaenoic acid (DHA). Low DHA intakes might explain subtle neurological deficits in PKU. We studied whether a DHA supply modified plasma DHA and neurological and intellectual functioning in PKU. In a double-blind multicentric trial, 109 PKU patients were randomized to DHA doses from 0 to 7 mg/kg&day for six months. Before and after supplementation, we determined plasma fatty acid concentrations, latencies of visually evoked potentials, fine and gross motor behavior, and IQ. Fatty acid desaturase genotypes were also determined. DHA supplementation increased plasma glycerophospholipid DHA proportional to dose by 0.4% DHA per 1 mg intake/kg bodyweight. Functional outcomes were not associated with DHA status before and after intervention and remained unchanged by supplementation. Genotypes were associated with plasma arachidonic acid levels and, if considered together with the levels of the precursor alpha-linolenic acid, also with DHA. Functional outcomes and supplementation effects were not significantly associated with genotype. DHA intakes up to 7 mg/kg did not improve neurological functions in PKU children. Nervous tissues may be less prone to low DHA levels after infancy, or higher doses might be required to impact neurological functions. In situations of minimal dietary DHA, endogenous synthesis of DHA from alpha-linolenic acid could relevantly contribute to DHA status.